Ineffectiveness of hepatitis B vaccination in cirrhotic patients waiting for liver transplantation - Edith Villeneuve; Jean Vincelette; Jean-Pierre Villeneuve (Canadian Journal of Gastroenterology)
Cirrhotic patients who undergo liver transplantation are at risk of acquiring de novo hepatitis B virus (HBV) infection at the time of transplantation. It is common practice to immunize these patients against HBV, but the efficacy of vaccination is uncertain. The response to vaccination with a recombinant HBV vaccine was examined in 49 patients with cirrhosis before liver transplantation. Patients received three doses (20 µg) of Engerix-B (SmithKline Beecham) at zero, one and two months before transplantation, and their response was measured on the day of liver transplantation (9.3±1.2 months after the initial dose of vaccine). Results were compared with those reported in healthy adults vaccinated according to the same schedule. Fourteen of 49 cirrhotic patients (28%) developed antibodies to hepatitis B surface antigen (anti-HBs) levels of more than 10 U/L after vaccination compared with 97% of healthy controls. Four patients (8%) had anti-HBs levels of more than 100 U/L compared with 83% in healthy individuals. Mean anti-HBs titre in the 14 responders was 62 U/L compared with 348 U/L in controls. No factor was identified that predicted response to vaccination. One of 49 patients acquired de novo HBV infection at the time of liver transplantation. Current HBV vaccination of cirrhotic patients waiting for liver transplantation is ineffective, and new strategies need to be developed to increase the response rate.